The ESG disclosure and sustainable growth: Does profitability matter? - Zaky Machmuddah; Winarsih Winarsih; Anik Yuesti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2025)
This study aims to examine the role of sustainability disclosure—which includes Environmental Disclosure, Social Disclosure, and Governance Disclosure—in influencing profitability (ROE) and supporting the Sustainable Growth Rate (SGR) in multinational companies. The study uses panel data from 96 Asian multinational companies over a fiveyear period and is estimated using the Full Generalized Least Squares (Full GLS) method to address potential heteroskedasticity and autocorrelation commonly found in panel data. The findings indicate that there is no significant evidence that the three dimensions of sustainability disclosure directly enhance corporate profitability. However, profitability (ROE) is shown to contribute positively to the Sustainable Growth Rate. In addition, Social Disclosure and Governance Disclosure have a significant impact on promoting sustainable growth, while Environmental Disclosure does not show a significant effect. Another finding suggests that high leverage negatively affects the Sustainable Growth Rate, and the interaction between profitability and the three dimensions of sustainability disclosure collectively supports more sustainable growth. This study underscores the importance of integrating stable financial performance with sustainability disclosure strategies to support the continuous growth of companies.